2016
DOI: 10.1063/1.4953660
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity of bacteria—Open questions

Abstract: Morphological plasticity of bacteria is a cryptic phenomenon, by which bacteria acquire adaptive benefits for coping with changing environments. Some environmental cues were identified to induce morphological plasticity, but the underlying molecular mechanisms remain largely unknown. Physical and chemical factors causing morphological changes in bacteria have been investigated and mostly associated with potential pathways linked to the cell wall synthetic machinery. These include starvation, oxidative stresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…It is therefore possible that bacteria are able to shape filaments induced by protists by-products as a defense mechanism to avoid amoeba phagocytosis, which would up-take only the smaller bacteria as described previously [ 70 ]. Morphological plasticity as part of phenotypic heterogeneity has been poorly studied while it may play a functional role within isogenic bacterial populations (reviewed in [ 71 ]). Filamentous morphology is known to provide survival advantages in particular during environmental stress or the presence of antibiotics or predators (reviewed in [ 72 ]).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that bacteria are able to shape filaments induced by protists by-products as a defense mechanism to avoid amoeba phagocytosis, which would up-take only the smaller bacteria as described previously [ 70 ]. Morphological plasticity as part of phenotypic heterogeneity has been poorly studied while it may play a functional role within isogenic bacterial populations (reviewed in [ 71 ]). Filamentous morphology is known to provide survival advantages in particular during environmental stress or the presence of antibiotics or predators (reviewed in [ 72 ]).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility of an overestimation of the survivability of E. coli due to these changes in morphology that differed from the normal shape of cells in the control culture and used to establish the cytometry settings for measures; and even the yellow color of these more spherical cells, which indicates an intermediate stage on the path to death, could have contributed to this overestimation. Several reports have shown that bacterial morphological changes are indeed caused by environmental stress conditions (Shen and Chou, 2016 ), which happens especially in salty media and at low temperatures for gram-negative bacteria such as E. coli (Yang et al , 2016 ). In particular, different types of bacteria tolerant to high perchlorate concentrations became larger and morphologically aberrant (Oren et al , 2014 ), or aggregated into long cellular chains (Beblo-Vranesevic et al , 2017 ), when exposed to this salt.…”
Section: Discussionmentioning
confidence: 99%
“…The microscopic analysis of the coagulated media revealed a shortening of rods, which, according to [33], is characteristic of L. kefiri, as it has the ability to form short rods (3 nm) or long filaments (15 nm). Morphological change could affect the metabolism of L. kefiri and explain its biphasic growth [36]. Rajoka et al [37] found that L. kefiri is able to attach to the grain surface in Brazilian kefir and is important for the production of the kefiran polymer present in the kefir grain's structure, which could explain the coagulation of the media.…”
Section: Modeling Effect Of Ph and Temperature For L Caseimentioning
confidence: 99%